Investigating EFL Passionate Teachers In Teaching English Speaking Skills - Friska Agustin; Dr. H. Ali Akbarjono, M.Pd.; Feny Martina, M.Pd. (JPI : Jurnal Pustaka Indonesia, 2022)
This study investigated teachers' passion for teaching and learning, it seeks to determine the implications for academic performance in language majors in high schools. The purpose of this research is to find out how and what are the obstacles and solutions for EFL passionate teachers in teaching English speaking skills in language major at SMA N 4 Bengkulu. This research is a descriptive qualitative research. The results show that the teacher who teaches English, especially speaking skills in the language major, is indeed an EFL passionate teacher who has met the qualifications and criteria and is recognized as having a certificate. Researchers found at this point, teaching is no longer a job and becomes an inspiration for students. In addition, it encourages more active learning to speak and promotes intellectual and moral development.